Effects of Instructional Model on Concept Attainment in Mathematicson “SET” of the Tenth Grade Students - Tesdee, Chawit; Chaturanon, Wimonrat (Ratchaphruek Journal, 2015)
The purposes of this research were to study effects of attainment model’s concept of instruction and conceptual thinking ability and to compare learning achievement of mathematics “Set” and conceptual thinking ability of the tenth grade students between the group learning by a concept attainment model and the group learning by IPST teaching model. The subject was 89 tenth grade students at Datdaruni school in Chachoengsao province. Forty-five students were in the experimental group and forty-four students were in the controlled group. There were two categories of research instruments. The data collection instruments were mathematics “set” achievement test and conceptual thinking ability test. The experimental instruments were lesson plans of mathematics “set”. The duration of experiment was six weeks, total of twelve periods. The collected data were analyzed by arithmetic means ( ) standard deviation (S.D.), t-test (Independent-Samples). The research findings were summarized as follows: 1. Students learning by concept attainment model obligated mathematics “set” achievement were scores more than 60 percent of the total score and equal or more 60 percent of experimental group. 2. Students learning by concept attainment model obligated the learning achievement of mathematics “set” higher than students learning by IPST teaching model at.05 level of significance. 3. Students learning by concept attainment model gained conceptual thinking ability higher than students learning by IPST teaching model at.05 level of significance.